Nano-analytical Characterization of Breast Tissue Biopsies Reveals an Association between Spherical Nano and Micro Particles and Invasive Malignant Breast Tumours - Tsolaki,E; Doran,W; Overbeck,J; Magnani,L; Olivo,A; Herrmann,IK; Bertazzo,S (2020)
Summary The presence of calcifications on mammograms is a widely used diagnostic marker for breast cancer. While the clinicopathological analysis of breast tissue is well-developed, an in-depth characterisation of the properties of calcifications at the micro and nano scale remained elusive. In this work, we use nano-analytical methods to investigate the calcification present in healthy breast tissue, as well as in benign and malignant breast tumour tissue biopsies. While polycrystalline apatite with lower crystallinity can be found in all breast tissue samples, we show that magnesium-containing nano and micro spherical particles are found only in malignant invasive breast cancers. These particles concentration increases with cancer progression. The discovery of these spherical particles provides new insights into the characteristics of breast calcification associated with malignant tumours and opens new research pathways to a better understanding of breast tumours and their microenvironment in general.